Hemophagocytic Syndrome an Autopsy Case - Karayel, Ferah; Süner, Çiğdem; Yılmazer, Özhan; Çetin, Gürsel (The Bulletin of Legal Medicine, 2003)
Hemophagocytic Syndrome (HPS) is frequently fatal condition accompanied with fever, cytopenia, hepatosplenomegaly, abnormal liver function tests, hypertriglyceridemia and hypofibrinogenemia. The goal of this study is to present HPS which we encountered very often in pediatric autopsies and emphasize the necessity of collecting tissue specimens from bone marrow, spleen and lymph nodes by including this syndrome in differentiating autopsy diagnosis from situations with similar symptômes. This case was a four mounth old male child who was autopsied in The State Institute of Forensic Medicine, Istanbul. The child was presented without external trauma findings, small sized subarachnoidal hemorrages in brain, 0.5 cm in diameter atrial septal defect in the heart, and dappled atelectatic feature in both lungs were observed in gross examination. While liver was 380 gr in weight and showed colour changes to yellow, spleen was 320 gr in weight and showed no evidence of gross changing but severe congestion. No evidence of gross pathologic manifestations was found in other organs. The histopathological examination of the organs showed mononuclear inflammatory cell infiltration with histiocytic dominance in myocardium, lungs, brain, cerebellum, lymph nodes and bone marrow. Particularly in bone marrow specimens, there was phagocytosis of erythrocyte, polymorphonuclear leukocyte and lymphocyte in cytoplasm of some histiocytes. The infiltration showed granulomatous structures in brain and cerebellum. In lung specimens, that infiltration was accompanied with alveolitis, alveolar epithelial damage and hyaline membrane materials, but there was no viral inclusion. Liver, kidneys and spleen were not evaluated in detail because of autolysis. In the evidence of clinical and microscopical findings, the diagnosis was 'Hemophagocytic Syndrome'. Hemophagocytic Syndrome which could be secondary to a viral infection was considered the cause of death in this case showed no toxicological findings. In conclusion, we intended to emphasize again the scientific and ethical value of autopsy in similar rare cases which was treated but died without diagnose in several centers.Key Words: Bone marrow, hemophagocytic syndrome, autopsy
Keywords: bone marrow; hemophagocytic syndrome; autopsy